Identification of infants and preschool children at risk for asthma: predictive scores and biomarkers. Issue 2 (April 2016) - Wandalsen, Gustavo F.; Solé, Dirceu; Bacharier, Leonard B.
Abstract : Purpose of review: Predictive asthma scores and biomarkers are important tools that help many physicians in the identification of infants and preschool children at high risk for asthma. Our objective was to review recent data regarding this subject. Recent findings: Recently, two new predictive asthma scores were developed with some innovative features, such as the definition of scales of asthma risk. In a systematic review, 12 asthma-predictive models were identified with heterogeneous performance. Prospective studies have shown that elevated fractional concentration of nitric oxide (FeNO) is a strong risk factor for latter asthma among early wheezers, and a predictive asthma score with FeNO values has been proposed. Plasma cytokines and exhaled volatile organic compounds were also identified as potential asthma predictors. Summary: Predictive scores are simple, practical, and inexpensive tools to identify children at high risk for asthma at school age. Whereas some scores are better at identifying asthmatic children, others are better at excluding the diagnosis of asthma. Although promising, clear evidence for FeNO as a robust asthma predictor in comparison to clinical scores is still lacking. Specific IgE and eosinophil counts remain the most consistent biomarkers for the identification of children at risk for asthma, and further studies are necessary to clarify the role of other biomarkers.